Efeitos de uma intervenção precoce em pais gestantes acerca do desenvolvimento infantil e violência intrafamiliar - Gonzaga, Domitila Shizue Kawakami (2014)
Primary prevention aims to identify, remove or reduce the incidence of risk factors that produce conditions of adversity. These conditions enable the link with Special Education required, since researches on strategies that can minimize or prevent the impact and occurrence of environmental events in the typical child development are essential to prevent possible deficiencies. This research was divided into two studies, Study 1 and Study 2, wich aimed to develop, implement and assess an intervention with pregnant parents about child development and prevention of domestic violence against children. Study 1 participants were a teenager couple, both 20 years old and pregnant. It was used the CAP - Inventory (Children Abuse Potential) and KIDI (Knowledge of Infant Development Inventory), a Qualitative Inventory regarding differents aspects of the intervention from the parents point of view, and a field notebook for various notes during the intervention. The intervention program consisted of two thematic blocks: 1) Child Development (CD); and 2) Parental Practices (PP). 6 2- hour meetings have been conducted with the couple at their home. The meetings began and ended with the administration of the inventories in order to assess the intervention through pre, post, and followup test scores. Therefore, the two blocks had the same structure, namely: 1) pretest administration, 2) CD theoretical explanation, 3) CD practical approach, 4) PP theoretical explanation; 5) PP practical approach; and 6) posttest administration. Three months after the posttest, the instruments were readministered - that was referred to as the follow-up score. It was used a laptop, overhead projector, some illustrative videos, some toys such as dolls and their apparatus. The overall KIDI scores showed no changes from pre to posttest for both Father and Mother. Regarding the results of the CAP, both performances were low-risk at the three assessments. The qualitative data from the questionnaire showed that the intervention was assessed with the highest score on all criterias. Regarding Study 2, 8 pregnant mothers were recruited from a public healthcare system in a suburb of the city where the research was conducted, separated into experimental group (EG) and control group (CG) participated. Three mothers of GE and GC reported experiencing some form of violence during childhood. Regarding KIDI, three mothers of GE showed an increase in overall score on the post-test and two at follow-up had their scores even higher. In CAP, two GE mothers had scores above the cutoff score on the post-test, while at follow-up; three mothers were above the cutoff. Mothers of GE evaluated the intervention as "good" to "very good" in all aspects and the note given to group was 10. Two GC mothers in KIDI presented at posttest an increase in overall score and in the follow-up two mothers had overall scores increased. In CAP, two participants scored above the cutoff score at post-test, however at follow-up, all mothers had scores above the cutoff. The performance of GE participants in the KIDI may indicate that the intervention helped in some acquisition of knowledge about child development. GC Mothers, in contrast, had all the scores of the CAP Abuse above the cutoff score at follow-up, which may indicate a very positive point for intervention, since it can be attributed to participation in the group that some GE mothers had their scores reduced below the cutoff. On quantitative data, is perceived that the EG performed better than the GC, and whereas the means of GE in the post-test and follow-up are better than the pre-test. About the correlations of the categories of instruments KIDI and CAP, there was a negative correlation between standards and Abuse, Sorrow and Loneliness. The demographic data, there was a negative correlation between education and Abuse, Sorrow and Loneliness and positive between education level and Ego and Norms.Because of that, it is reiterate the importance of approaching mothers with knowledge about child development and appropriate parenting practices. It is noticed that for both the teen couple and the group of mothers, the intervention was positive, especially with the qualitative data, and the speeches of the participants of the two studies showed that the intervention had relevance.